2009
DOI: 10.4153/cmb-2009-008-0
|View full text |Cite
|
Sign up to set email alerts
|

Huber's Theorem for Hyperbolic Orbisurfaces

Abstract: Abstract. We show that for compact orientable hyperbolic orbisurfaces, the Laplace spectrum determines the length spectrum as well as the number of singular points of a given order. The converse also holds, giving a full generalization of Huber's theorem to the setting of compact orientable hyperbolic orbisurfaces.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 11 publications
(13 reference statements)
0
12
0
2
Order By: Relevance
“…It is not known whether the statement concerning nonisospectrality of manifolds and orbifolds remains true without the condition of a common Riemannian covering. Dryden and Strohmaier [9] showed that on oriented compact hyperbolic orbifolds in dimension two, the spectrum completely determines the types and numbers of singular points. Independently, this had also been shown by the first author together with P.G.…”
mentioning
confidence: 99%
“…It is not known whether the statement concerning nonisospectrality of manifolds and orbifolds remains true without the condition of a common Riemannian covering. Dryden and Strohmaier [9] showed that on oriented compact hyperbolic orbifolds in dimension two, the spectrum completely determines the types and numbers of singular points. Independently, this had also been shown by the first author together with P.G.…”
mentioning
confidence: 99%
“…By Theorem 2.2, since X(Γ) and X(Γ ) are representation equivalent, they are isospectral with respect to the Laplace operator. When dim(X(Γ)) = dim(X(Γ )) = 2, it follows that X(Γ) and X(Γ ) are length isospectral by work of Dryden and Strohmaier [34] (see also Doyle and Rossetti [32,33]), so in particular L(X(Γ)) = L(X(Γ )). When dim(X(Γ)) = dim(X(Γ )) = 3, it follows from the trace formula of Duistermaat and Guillemin [36] (see also Prasad and Rapinchuk [72, Theorem 10.1], and in the orbifold case Elstrodt, Grunewald, and Mennicke [39, p. 203]) that X(Γ) and X(Γ ) have the same sets of lengths of closed geodesics, considered without multiplicity.…”
Section: Isometriesmentioning
confidence: 99%
“…However, this procedure changes the spectrum, and indeed "one can hear the orders of the cone points of orientable hyperbolic 2-orbifold" [33]. For further discussion on this point, see also work of Dryden [34], Dryden, Gordon, Greenwald, and Webb [35,Section 5], and Gordon and Rossetti [49,Proposition 3.4]. )…”
mentioning
confidence: 99%
“…En ce qui concerne le rapport entre le spectre du Laplacien et le spectre des longueurs on renvoie aux travaux de W. Müller [21,1992] pour le cas non compact et à ceux de E. Dryden et A. Strohmaïer [14,2004], [15] pour le cas des orbifolds.…”
Section: Variantesunclassified